Hydroxychloroquine reduces metastatic tumor burden in pancreatic adenocarcinoma through myeloperoxidase inhibition - Britney Niemann; Pavan Rao; Quinn Hopen; Kaitlyn Landreth; Angisha Basnet; Werner Geldenhuys; Tracy W. Liu; Brian A. Boone (Journal of Inflammation)
Abstract Background Metastatic pancreatic adenocarcinoma has a 5-year survival of only 3%. Neutrophil extracellular traps are formed when neutrophils expel their intracellular contents and have been intricately linked to metastases. Hydroxychloroquine is an FDA-approved anti-malarial drug and neutrophil extracellular trap inhibitor with high potential for clinical translation. This study investigates the impact of hydroxychloroquine treatment on pancreatic metastases. Results Hydroxychloroquine reduced metastatic tumor burden via a neutrophil extracellular trap independent mechanism and resulted in prolonged survival. Hydroxychloroquine inhibited the function of myeloperoxidase in vitro via direct binding with a Kd of 9.74 mM. Myeloperoxidase inhibition via hydroxychloroquine in vivo was the direct result of suppressed activity. Hydroxychloroquine mediated myeloperoxidase inhibition was also demonstrated in metastatic pancreatic adenocarcinoma patients receiving neoadjuvant chemotherapy. Conclusion Hydroxychloroquine suppressed pancreatic metastases growth through myeloperoxidase inhibition, leading to a significant increase in survival. Corroborative data supports this mechanism in metastatic pancreatic adenocarcinoma patients treated with hydroxychloroquine. These data provide important insight into the role of myeloperoxidase in pancreatic metastases and the potential use of hydroxychloroquine in metastatic pancreatic adenocarcinoma treatment.